The JAK1 Selective Inhibitor ABT 317 Blocks Signaling Through Interferon-γ and Common γ Chain Cytokine Receptors to Reverse Autoimmune Diabetes in NOD Mice - Ge, Tingting; Jhala, Gaurang; Fynch, Stacey; Akazawa, Satoru; Litwak, Sara; Pappas, Evan G.; Catterall, Tara; Vakil, Ishan; Long, Andrew J.; Olson, Lisa M.; Krishnamurthy, Balasubramanian; Kay, Thomas W.; et al. (Frontiers in Immunology, 2020)
Cytokines that signal through the JAK-STAT pathway, such as interferon-gamma (IFN-g) and common gamma chain cytokines, contribute to the destruction of insulin-secreting beta cells by CD8+ T cells in type 1 diabetes (T1D). We previously showed that JAK1/JAK2 inhibitors reversed autoimmune insulitis in non-obese diabetic (NOD) mice and also blocked IFN-g mediated MHC class I upregulation on beta cells. Blocking interferons on their own does not prevent diabetes in knockout NOD mice, so we tested whether JAK inhibitor action on signaling downstream of common gamma chain cytokines, including IL-2, IL-7 IL-15 and IL-21, may also affect the progression of diabetes in NOD mice. Common gamma chain cytokines activate JAK1 and JAK3 to regulate T cell proliferation. We used a JAK1-selective inhibitor, ABT 317, to better understand the specific role of JAK1 signaling in autoimmune diabetes. ABT 317 reduced IL-21, IL-2 and IL-7 signaling in T cells and IFN-g signaling in beta cells, but ABT 317 did not affect GM-CSF signaling in granulocytes. When given in vivo to NOD mice, ABT 317 reduced CD8+ T cell proliferation as well as the number of KLRG+ effector and CD44hiCD62Llo effector memory CD8+ T cells in islets and spleen. ABT 317 also prevented MHC class I upregulation on beta cells. Newly diagnosed diabetes was reversed in 94% NOD mice treated twice daily with ABT 317. Our results indicate that ABT 317 blocks common gamma chain cytokines in lymphocytes and interferons in lymphocytes and beta cells and are thus more effective against diabetes pathogenesis than IFN-g receptor deficiency alone. Our studies pave the way for use of this class of drug in clinical trials for type 1 diabetes.